2012
DOI: 10.1038/nature10989
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic autism exomes reveal a highly interconnected protein network of de novo mutations

Abstract: It is well established that autism spectrum disorders (ASD) have a strong genetic component. However, for at least 70% of cases, the underlying genetic cause is unknown1. Under the hypothesis that de novo mutations underlie a substantial fraction of the risk for developing ASD in families with no previous history of ASD or related phenotypes—so-called sporadic or simplex families2,3, we sequenced all coding regions of the genome, i.e. the exome, for parent-child trios exhibiting sporadic ASD, including 189 new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

72
1,896
8
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,001 publications
(1,993 citation statements)
references
References 51 publications
72
1,896
8
17
Order By: Relevance
“…Consistent with this view, the genes differentially expressed in cell lines of 16p11.2 600 kb BP4-BP5 carriers were enriched not only in pathways relevant to neurodevelopmental defects and ciliopathy but also in genes involved in phosphoinositide signaling. 22 Of note, germline variants in PTEN present the ASD, obesity, and macrocephaly triad of phenotypes, [66][67][68][69][70] whereas those in the Ras/MAPK signaling pathway are associated with social impairment. 71 The interactions observed at this cluster of genes, both at the chromatin and genetic level, suggest that the CNVprone non-overlapping loci at 16p11.2 should be approached and studied as ''connected regions'' rather than completely independent entities.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, the genes differentially expressed in cell lines of 16p11.2 600 kb BP4-BP5 carriers were enriched not only in pathways relevant to neurodevelopmental defects and ciliopathy but also in genes involved in phosphoinositide signaling. 22 Of note, germline variants in PTEN present the ASD, obesity, and macrocephaly triad of phenotypes, [66][67][68][69][70] whereas those in the Ras/MAPK signaling pathway are associated with social impairment. 71 The interactions observed at this cluster of genes, both at the chromatin and genetic level, suggest that the CNVprone non-overlapping loci at 16p11.2 should be approached and studied as ''connected regions'' rather than completely independent entities.…”
Section: Discussionmentioning
confidence: 99%
“…Besides structural rearrangements, other abnormalities of chromosomal numbers or aneuploidies are detected in ASD including trisomy 21, Turner syndrome (45, X), and Klinefelter syndrome (47, XXY; Devlin & Scherer, 2012). Thanks to the comparative genomic hybridization (CGH) technique or SNPs array, CNVs were also found in multiple chromosomal regions at 1q21.1, 16p11.2, 17q12, and 22q11.2 (Jacquemont et al., 2006; Marshall et al., 2008; Matsunami et al., 2013; O'Roak et al., 2012; Pinto et al., 2010; Sebat et al., 2007). Further studies supported the association with ASD of two recurrent de novo CNVs at 16p11.2 (duplication and deletion) and 7q11.23 (duplication; Levy et al., 2011; Sanders Stephan et al., 2011).…”
Section: Reviewmentioning
confidence: 99%
“…A chromosomal translocation of 2p:12p resulting in a deletion of both genes ( CACNA1C and CACNA2D4 ) was detected in two ASD‐affected individuals (Smith et al., 2012). Furthermore, a whole‐exome sequencing study identified de novo rare alleles in α 1 subunit loci CACNA1D and CACNA1E (O'Roak et al., 2012; Pinggera et al., 2015). The α 1 subunit (Ca v 1.3) of L‐type channels plays an important role in neuronal signaling and in brain function including memory and behavior (Pinggera et al., 2015).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Recent studies have demonstrated that ASDs can be caused by rare, highly penetrant point mutations, deletions, duplications and larger chromosomal abnormalities that can either arise de novo or be inherited. [3][4][5][6][7][8][9] Known monogenic disorders account for 2-5% of syndromic cases; fragile X syndrome is usually the most common cause, followed by PTEN macrocephaly syndrome and tuberous sclerosis, each accounting for o1% of individuals with ASD. 1,10 Large copy number variants (CNVs) are found in 5-10% of autistic patients, especially in those with syndromic ASDs.…”
Section: Introductionmentioning
confidence: 99%